1989
DOI: 10.1097/00006842-198905000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The association of peripheral arterial disease with hostility in a young, healthy veteran population.

Abstract: The association of peripheral arterial disease (PAD) with hostility, a component of Type A behavior, has not been investigated. Previous studies have found an association between coronary arterial disease and hostility. We used Doppler tests to define PAD as consisting of a resting index less than 0.9, absence of posterior tibial waveform, or presence of a femoral bruit. Among 4,462 male veterans, the prevalence and odds ratio of PAD increased statistically significantly with an increase in the Cook-Medley hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The increase in risk of PAD persisted after adjusting for smoking, family history and other risk factors, [29] Our finding that only around 3% of both veterans and non-veterans with PAD had comorbid PTSD indicates that although this was not a major risk factor in our study, the prevalence of anger in military personnel [30] suggests that the association with hostility may be a contributory factor.…”
Section: What Is Already Known On This Topicmentioning
confidence: 60%
“…The increase in risk of PAD persisted after adjusting for smoking, family history and other risk factors, [29] Our finding that only around 3% of both veterans and non-veterans with PAD had comorbid PTSD indicates that although this was not a major risk factor in our study, the prevalence of anger in military personnel [30] suggests that the association with hostility may be a contributory factor.…”
Section: What Is Already Known On This Topicmentioning
confidence: 60%
“…In a random sample of more than 4,000 male veterans ranging in age from 31 to 46 years, Joesoef, Wetterhall, DeStefano, Stroup, and Fronek (1989) found a small but significant association between Ho scores and the prevalence of peripheral artery disease. In a sample of more than 3,700 Finnish male twins ages 40 to 59 years, scores on a self-report measure of anger proneness, irritability, and argumentiveness were associated with increased prevalence of angina (Koskenvuo et al, 1988).…”
Section: Cross-sectional Studiesmentioning
confidence: 89%
“…The Cook and Medley Hostility Scale (HO) [9] is a self-reported general measure of cynical hostility [10], which has been success fully used in several studies of the health con sequences of hostility, especially in regard to cardiovascular disease (CVD) [11][12][13]; al though other studies failed to replicate the same results [14][15][16], Although several studies on the HO con struct suggested the presence of one main fac tor labelled cynicism [17,18], three main aspects of hostility have been proposed as concepts to be considered as separate in the HO [19][20][21], The cognitive component con sists of negative beliefs about the trustworthi ness of others. The affective component in cludes negative emotional states like anger, irritability, and contempt associated with so cial relationships.…”
Section: Introductionmentioning
confidence: 99%